2004
DOI: 10.1021/ja047291m
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Interstrand Hydrophobic Packing Interactions within Unnatural DNA Base Pairs

Abstract: As part of an effort to expand the genetic alphabet, we have evaluated a large number of predominantly hydrophobic unnatural base pairs. We now report the synthesis and stability of unnatural base pairs formed between simple phenyl rings modified at different positions with methyl groups. Surprisingly, several of the unnatural base pairs are virtually as stable as a natural base pair in the same sequence context. The results show that neither hydrogen-bonding nor large aromatic surface area are required for ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 46 publications
4
44
0
1
Order By: Relevance
“…8,9,11,14,15,20,22,[28][29][30][31][32][33][34] From these, 60 were collected ( Figure 2) and their phosphoramidites incorporated into the 3' end of a 24-mer primer oligonucleotide and at the 24 th position of a complementary 45-mer template oligonucleotide. Hybridization of any given primer strand with any template strand results in an unnatural primer terminus (dX:dY, where dX is the primer nucleobase and dY is the template nucleobase).…”
Section: Screening For Unnatural Base Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,11,14,15,20,22,[28][29][30][31][32][33][34] From these, 60 were collected ( Figure 2) and their phosphoramidites incorporated into the 3' end of a 24-mer primer oligonucleotide and at the 24 th position of a complementary 45-mer template oligonucleotide. Hybridization of any given primer strand with any template strand results in an unnatural primer terminus (dX:dY, where dX is the primer nucleobase and dY is the template nucleobase).…”
Section: Screening For Unnatural Base Pairsmentioning
confidence: 99%
“…Indeed, several nucleotides bearing predominantly hydrophobic nucleobase analogs have been shown to pair stably and selectively in duplex DNA. 13,14 We, 9,10,15,16 and others, 8,12,[17][18][19] have shown that hydrophobic forces are also sufficient for the enzymatic synthesis of an unnatural base pair by incorporation of an unnatural nucleoside triphosphate against a template unnatural nucleotide; however, synthesis beyond the unnatural base pair, i.e. extension, tends to be relatively inefficient and generally limits the utility of these base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…This may also hold true for the MMAN self-pair with only 4-position methyl groups, which is more stable than the MAN self-pair, which has no methyl groups at the 4-position, and the DMMAN self-pair, which has an additional 5-position methyl group. The stability of the unnatural self-pairs of MAN, MMAN, and DMMAN was lower than that of AM, ADM, and even simple benzene (T m = 52.8 o C) 10 self-pairs. This result indicates that the methylation at the ortho-amine probably disrupts the optimized packing of the 2-position amine group in the interbase interface and hence significantly destabilized the self-pairs.…”
Section: Scheme 1 Synthesis Of Aminobenzene Derivatized Nucleotidesmentioning
confidence: 81%
“…Romesberg, Schultz, and coworkers have synthesized a number of analogues such as 7-azaindole (7-AI), propynylisocarbostyrile (PICS) (Fig. 13-5) as well as some fluoroaromatic analogues [68] and evaluated them as potential self-pairing nucleosides [69,70]. Various of the analogues prepared are also recognized with reasonable selectivity by DNA polymerases [49,68,71].…”
Section: Altered Basesmentioning
confidence: 99%